Optimalization of Coping Nurses to Overcoming Anxiety in the Pandemic of Covid-19 in Era New Normal - Jek Amidos Pardede; Budi Anna Keliat; Rani Kawati Damanik; Adventy Riang Bevy Gulo (Global Health Science Group, 2020)
Coronavirus is a virus that infects the respiratory system. Coronavirus is troubling the public with signs of fear and anxiety. Likewise, experienced by nurses who work in health services so that it needs to be given support to strengthen coping to keep treating patients without any difficulties. These community service activities are carried out using zooming and live streaming on YouTube to maintain the health protocol recommended by the government. The purpose of this activity is to provide knowledge and motivation for nurses to strengthen coping or self-efficacy in carrying out activities in the health service. The results of these community service activities are expected to increase the motivation of 1,120 nurses in using positive and adaptive coping in their daily activities and in health services.